Women's perception of risks of adverse fetal pregnancy outcomes: a large-scale multinational survey - Irene Petersen; Hedvig Nordeng; Angela Lupattelli; Rachel L McCrea (BMJ Open)
Objective To determine pregnant women and new mothers’ perception of risks in pregnancy.Design, settings and participants This was a large-scale multinational survey including 9113 pregnant women and new mothers from 18 countries in Europe, North America and Australia.Main outcomes Risk perception scores (0–10) for harmful effects to the fetus were derived for: (1) medicines (over-the-counter medicine and prescribed medicine), (2) food substances (eggs and blue veined cheese), (3) herbal substances (ginger and cranberries) (4) alcohol and tobacco, and (5) thalidomide.Results Overall, 80% (6453/8131) of women perceived the risk of giving birth to a child with a birth defect to be ≤5 of 100 births. The women rated cranberries and ginger least harmful (mean risk perception scores 1.1 and 1.5 of 10, respectively) and antidepressants, alcohol, smoking and thalidomide as most harmful (7.6, 8.6, 9.2 and 9.4 out of 10, respectively). The perception varied with age, level of education, pregnancy status, profession and geographical region. Noticeably, 70% had not heard about thalidomide, but of those who had (2692/9113), the risk perception scores were 0.4–0.5 points lower in women below 25 years compared to women aged 26–30 years.Conclusions In general, women perceived the risks of giving birth to a child with birth defects low, but there were substantial disparities between women's perceived risks and the actual risks when it comes to over-the-counter agents against nausea and prescribed medication. The study revealed that few women knew of thalidomide, suggesting that the general awareness among women of the teratogenic effects of thalidomide is declining, but it has left a general scepticism about safety of medication in pregnancy. This may have some severe consequences if women are left without medical treatments in pregnancy.